Dissection and engineering of theEscherichia coli formate hydrogenlyase complex. Issue 20 (7th September 2015) - McDowall, Jennifer S.; Hjersing, M. Charlotte; Palmer, Tracy; Sargent, Frank
Abstract : The Escherichia coli formate hydrogenlyase (FHL) complex is produced under fermentative conditions and couples formate oxidation to hydrogen production. In this work, the architecture of FHL has been probed by analysing affinity‐tagged complexes from various genetic backgrounds. In a successful attempt to stabilize the complex, a strain encoding a fusion between FdhF and HycB has been engineered and characterised. Finally, site‐directed mutagenesis of the hycG gene was performed, which is predicted to encode a hydrogenase subunit important for regulating sensitivity to oxygen. This work helps to define the core components of FHL and provides solutions to improving the stability of the enzyme. Abstract : Gene deletions identify the stable core complex of bacterial formate hydrogenlyase. Synthetic biology approaches generated an active, stable fusion protein. Attempts to engineer O2 ‐tolerance into FHL were only partly successful.